Measuring and Analyzing the Impact of Some Economic Variables on Public Liquidity in Iraq for the Period (2004-2020) - Thamer Saleh*, Qutaiba; Mustafa Abdul Hameed, Manahel (Journal of Economics and Administrative Sciences, 2024)
Purpose: The research aims to diagnose the extent of the central bank's control over public liquidity by integrating the arrangement of monetary and macro indicators in the economy, with the aim of improving the management of public liquidity within the Iraqi economy.Theoretical framework: The research dealt with the study of analyzing the impact of some economic variables, such as public debt, gross domestic product, currency window, local credit, and general liquidity in Iraq, by using the linear regression model to describe the relationship between economic phenomena, specifically between the independent variables and the dependent variable. From here, the research problem can be formulated through interventions in the work of monetary policy tools. Therefore, it is necessary to determine the effects of financial authority on the economy by measuring the variance in the impact left by monetary tools, which is reflected in the macroeconomic variables, which are considered indicators of the efficiency of economic policy.Design/methodology/approach: The study measures and analyses monetary data from (2004-2020) using the real-time equation model SURE to measure the impact of inward ratios (legal reserve, rediscount rate, currency window, public debt, GDP, domestic credit), on Iraq's public liquidity.Findings: Using quantitative methods to achieve results enables us to obtain more accurate estimates than analytical results. Therefore, given the varying degrees of stability and the multiple equations included in the model, simultaneous equations models were adopted to measure the impact of monetary policy variables on the size of financial liquidity in the economy and to guide the Iraqi economy in specific directions. This approach is in line with the country's monetary policy.Research, Practical & Social Implications: The results emphasize the need to integrate macroeconomic indicators into a standard model for measuring and analyzing public liquidity and understanding management.Originality/value: The originality of the current research is highlighted by the analysis method used, which is the ordinary least squares (OLS) method, which is a widely used method in measuring and estimating linear regression, which forms the basis for many standard economic models. The linear regression model was used to describe the relationship between economic phenomena, specifically between the independent and dependent variables.